Produk Cartesius Semipgrup Smarandache - Yuliyanti Dian Pratiwi (Jurnal Matematika, 2012)
Smarandache semigroups is an expansion of semigroup structure, by taking a proper subset of semigroups which is in form of group. But, a proper subset which is in form of group cannot always be found in semigroups. Therefore, we need necessary requirements and prosperous requirements in the Smarandache semigroups. Besides, this study also shows some kinds of Smarandache semigroups, which have specific characteristics, namely Smarandache commutative semigroups and Smarandache cyclic semigroups. Then, by the definitions, we will investigate the form of its Cartecius product.